Web-Based Classroom Loan Information System (Case Study Student Organizations at Muhammadiyah University of Sidoarjo) - Alfian Maulana Fajar; Ika Ratna Indra Astutik (Procedia of Engineering and Life Science, 2021)
This research was aimed to create a website based information system that can be used for summarize the flow and facilitate borrowing space in the University of Muhammadiyah Sidoarjo by student organizations. The research method used by researchers is the waterfall method, but the data collection technique uses several ways, namely observation, interviews, and also literature study. Researchers made observations in student organizations to obtain data, in addition to met with the Directorate of Asset and Environmental Management to obtain data. The result of this research is that student organizations can borrow space online, and make it easier to recap data and also minimize duplicate data in the system. With more efficient procedures, the borrowing process becomes easier and more practical